Group B streptococcal neonatal infections in Rio Grande do Sul, Brazil - MIURA, Ernani (2001)
Group B Streptococcus is the most common pathogen found in neonatal sepsis in North America. OBJECTIVES: We describe 15 cases of neonatal infections by Group B Streptococcus (Streptococcus agalactiae) at a Neonatal Intensive Care Unit of a public and teaching hospital. METHODS: We conducted a study at Hospital de Clínicas de Porto Alegre, from January 1st, 1996 to June 30, 1999. Diagnosis of neonatal infection was established according to the findings of Group B Streptococcus in blood culture associated with alterations resembling sepsis on the basis of clinical picture and laboratory findings. RESULTS: Fifteen cases of neonatal infections by Group B Streptococcus were detected. Eleven cases consisted of early-onset sepsis, 2 cases of occult bacteremia and 2 cases of late-onset sepsis. Eight cases had septic shock (53%), 8 cases had pneumonia (53%), and 4 cases had meningitis (27%). Fourteen cases were diagnosed from a positive blood culture, and 1 case from evidence of these bacteria in pulmonary anatomopathological examination. Thirteen cases (87%) were diagnosed before 72 hours of life. We had 3 deaths (20%), and 3 cases of meningitis developing neurological deficits. CONCLUSIONS: Streptococcus Group B is one of the most important pathogens in the etiology of early-onset neonatal sepsis at our hospital, with high mortality and morbidity. However, we do not know the incidence of GBS neonatal infections at other hospitals. More data are needed to establish a basis for trials of different strategies to reduce these infections.